The value of preoperative lymphocytes-to-monocytes ratio in predicting lymph node metastasis in gastric cancer - Du, Dexiao; Han, Ziliang; Lian, Dongbo; Amin, Buhe; Yan, Wei; Zhang, Nengwei (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: This study was aimed to evaluate value of preoperative lymphocytes-to-monocytes ratio (LMR) as a predictor for lymph node metastasis in gastric cancer. Methods: Patients with pathologically diagnosed malignant gastric tumor were reviewed retrospectively. Patients’ demographic data, clinical manifestations and LMR were collected. The postoperative pathology data including the tumor size, tumor sites, differentiation degree of tumor, depth of tumor invasion, metastatic lymph nodes, total dissected lymph nodes, distant metastasis, vessel carcinoma embolus, neural invasion, Lauren’s classification, Ki-67 and TNM stage were collected. Receiver operating characteristic curve (ROC) was used to determine the cut-off point of LMR. The association between LMR and the clinicopathologic factors was further analyzed. Results: A total of 177 subjects were enrolled into the study. LMR =3.79 was used as cut-off point; the patients with LMR ≥3.79 were classified as high-LMR group (123 cases) and the patients with LMR